Peran Kepemimpinan Efektif dalam Meningkatkan Kinerja Administrasi Publik di Perguruan Tinggi - Everistus Ricardus (PT PUSTAKA CENDEKIA GROUP, 2024)
This study aims to analyze the role of leadership in improving public administration performance in universities in Merauke, South Papua, and to formulate effective strategies to overcome the governance challenges faced. Using a qualitative approach and case study method, this study explores the views and experiences of university leaders, administrative staff, and related stakeholders regarding public administration management influenced by leadership. Descriptive analytical research design is used to describe leadership characteristics and analyze their impact on public administration effectiveness. This study was conducted in universities in Merauke that face challenges related to limited resources and infrastructure. Data were collected through in-depth interviews, Focus Group Discussions (FGD), observation, and documentation. Thematic analysis was used to identify key themes related to leadership and administrative performance. The results of the study indicate that leadership in universities in Merauke is still dominated by a bureaucratic style that is less flexible, inhibiting innovation and efficiency. Despite efforts to implement transformational leadership, resistance to change and limited resources are major obstacles. Recommendations for this study include changes in inclusive leadership patterns, development of information technology, and increased collaboration between stakeholders to improve the quality of academic services and operational efficiency in universities. With the implementation of the right policies, universities in Merauke are expected to be ready to face the challenges of globalization of education.